INTERFERENSI BAHASA ARAB TERHADAP BAHASA INDONESIA PADA TERJEMAHAN AL-QUR’AN KEMENAG RI EDISI PENYEMPURNAAN 2019 - Maulana Muqsit; Moch. Syarif Hidayatullah; Ahmad Hifni; Waki Ats Tsaqofi; Darsita Suparno; Driss Attih (Afshaha: Jurnal Bahasa dan Sastra Arab, 2025)
This research explores the trend of translated works in Indonesian literature, emphasizing the importance of translation as a bridge for readers who do not understand the source text. Translated works, such as the Qur'an, play a crucial role in expanding cross-cultural understanding and communication. The translation of the Qur'an by the Ministry of Religious Affairs of the Republic of Indonesia has always had high attention and become the main reference for Muslims in Indonesia. However, several studies have found that despite the increasing demand for translations, the quality of translations remains a challenge. Factors such as diction errors, interference, and faux amis are often found, which interfere with the reader's understanding of the target text. The researcher in this study, analyzed the forms of interference found in the latest edition of the Ministry of Religious Affairs' Qur'anic translation using a qualitative descriptive method. Data were collected from reliable sources, including the official website of the Ministry of Religious Affairs and various related literatures. Observation techniques were used to identify and record the forms of interference in the translation, which were then analyzed and classified. The results of the analysis show the presence of interference in various linguistic aspects, such as lexical and syntax.